Statistics on Public Expenditures for Economic Development by Economic Classes (SPEED-EC) - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
This dataset presents government expenditures by economic classification of expenses rather than by functional classification as it was the case in previous versions. The dataset includes sixteen economic categories and sub-categories of government expenses. The Government Finance Statistics Manual 2014 (IMF, 2014) provides details of the economic classification of expenditures (See particularly Chapter 6). According to IMF 2014 (page 114), “the economic classification of expense identifies the types of expense incurred according to the economic process involved”. Below is a list of the economic categories and sub-categories of government expenses included in the dataset along with some definitions taken from the IMF Government Finance Statistics Manual. In brackets are the corresponding variables names used in the dataset. Total expense (expense) which is the sum of all economic categories listed below Compensation of employees (comp_emp): Compensation of employees is the total remuneration, in cash or in kind, payable to an individual in an employer-employee relationship in return for work performed by the latter during the reporting period… Compensation of employees comprises wages and salaries and employers’ social contributions payable by employers on behalf of employees to social insurance schemes (IMF 2014, pages 115 and 116). Consumption of fixed capital (cons_cap): Consumption of fixed capital is the decline, during the course of the reporting period, in the current value of the stock of fixed assets owned and used by a government unit as a result of physical deterioration, normal obsolescence, or normal accidental damage (IMF 2014, pages 124-125). Grants expense (gt_exp): Grants expenses are transfers payable by government units to other resident or nonresident government units or international organizations and that do not meet the definition of a tax, subsidy, or social contribution (IMF, page 134). Grants expense to foreign government (gt_exp_for) Grants expense to other general government (gt_exp_gov) Grants expense to international organization (gt_exp_int) Interest expense (int_exp): Interest expense is a form of investment income that is receivable by the owners of certain kinds of financial assets (SDRs, deposits, debt securities, loans, and other accounts receivable) for putting these financial and other resources at the disposal of another institutional unit (IMF, page 127). Interest expense to other general government (int_exp_gov) Interest expense to non-residents (int_exp_nr) Interest expense to residents other than general government (int_exp_res) Other expense (ot_exp): Other expense comprises property expense other than interest, transfers not elsewhere classified, and amounts payable in respect of premiums, fees, and claims payable related to nonlife insurance and standardized guarantees (IMF, page 137). Social benefits expense (soc_exp): Social benefits expense are current transfers receivable by households intended to provide for the needs that arise from social risks—for example, sickness, unemployment, retirement, housing, education, or family circumstances (IMF, page 13). Subsidies expense (sub_exp): Subsidies expense are current unrequited transfers that government units make to enterprises on the basis of the level of their production activities or the quantities or values of the goods or services they produce, sell, export, or import (IMF, page 131). Subsidies expense to other sectors (sub_oth) Use of goods and services (use_gs): Use of goods and services consists of the value of goods and services used for the production of market and nonmarket goods and services (IMF 2014, page 120).